PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA BAGIAN TICKETING DI PT. HARYONO TOURS AND TRAVEL SURABAYA - AJENG NOVITA, ELFANDA (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2013)
ABSTRACT Increase the extent of existing work in this world more and more styles of leadership that exist for the welfare of employees and office progress. Therefore, management needs to create the motivation of the employees. Employee job satisfaction influenced the attitude of many leaders in his leadership. Leadership participation provide job satisfaction for employees because employees actively participate in giving his opinion to determine corporate policy. Formulation of the problem in this research is the influence of leadership style How, How does work motivation, and is the effect of leadership style and work motivation on employee job satisfaction in the ticketing section Haryono tours and travel PT Surabaya. Of the results of the study were analyzed by using the t test the influence of leadership style on job satisfaction produces t = 2,063 > t table 2,026 with a significance value = 0,046 < 0,05. T test the influence of motivation and job to job satisfaction produces t = 3.181 > t table 2,026 with a significance value = 0,003 < 0,05 while f test style influence leadership and work motivation on job satisfaction produces count f = 18,965 > 3,252 f table with value significance = 0,000 < 0,05. So it can be concluded that the style of leadership and motivation have a significant effect on job satisfaction of employees at PT. Haryono Tours and Travel Surabaya. Keywords: Leadership styles, Motivation, Job Satisfaction.